Gnoseological Aspects of Philosophical Problems of Linguistics - Eshonova Dilnoza Abrorovna (Genius Journals, 2021)
The article is devoted to the basic questions that language and linguistics put to philosophy as an activity of determining the essence of things. If all the problems in the philosophy of language are grouped around central contradictions, then the philosophy of linguistics is called to answer questions about how knowledge of language is expressed and how scientific theories are structured. At the same time, the specificity of the philosophy of linguistics is largely related to the specificity of its object.
Keywords: Speech; language; picture of the world; mutual understanding